(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this paper, I develop the theoretical foundations that politically underpinned the research and exhibition project “The Future Has Already Happened: Maroon Antifuturism.” I make this effort in the hope that the critical review of the field of art that we developed, as well as the positions of meaning we adopted, will contribute to other efforts to decolonize artistic practice.